Mass propagation of Bambusa bambos (L.) Voss through in vitro culture - Raju, Raihan I; Roy, Shyamal K (Jahangirnagar University Journal of Biological Sciences, 2017)
Protocol for mass propagation of Bambusa bamboos (L.) Voss was developed through in vitro culture. Nodal segments containing pre-existing axillary bud, after surface sterilization, were inoculated on liquid Murashige and Skoogs (MS) basal medium containing different concentrations and combinations of cytokinins (BAP, TDZ and Kn). The highest direct shoot induction (90%) was obtained in the MS liquid medium supplemented with 2.0 mg/l BAP and 1.0 mg/l TDZ with maximum average number of shoots (3.14 ± 0.06) per explant. Highest shoot multiplication (16.58 ± 0.24 shoots per culture) with highest average shoot length (9.21 ± 0.13 cm) was obtained when in vitro raised shoots were cultured in gelrite gelled MS medium in conjunction with 2.0 mg/l BAP and 1.0 mg/l TDZ. Incorporation of 10% coconut water with 4% sucrose in the above mentioned medium resulted satisfactory shoot growth and development with an average 26.7 ± 0.60 shoots per culture. For root induction, in vitro raised shoots were divided into clumps of 4-5 shoots in each clump and transferred onto both liquid and gelled half-strength MS medium containing different concentrations and combinations of auxins (IBA and NAA). Maximum rooting (86.67%) was achieved in half-strength of MS medium fortified with 2.5 mg/l IBA and 2.5 mg/l NAA with an average 8.72 ± 0.42 root per shoot. The rooted plantlets were then transferred to polybags containing garden soil, sand and compost mixture with 1:1:1 ratio. After a month the hardened plantlets were then transferred to the larger pots containing garden soil and compost with 1:1 ratio for sufficient growth and finally transplanted to the field. In this process, the highest 100% survivability was recorded from well-established rooted plantlets. The regenerated plants showed well developed root and shoot systems in field condition. Jahangirnagar University J. Biol. Sci. 5(2): 15-26, 2016 (December)